Mathematical literacy and learning style: An analysis of students’ PISA performance using Kolb’s framework - Putri, Suci Kirani Aprilia; Elvi, Mariyanti; Siregar, Nur Asma Riani (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aimed to investigate the mathematical literacy of Grade VIII junior high school students based on their learning styles, as categorized by David Kolb. A qualitative approach with a descriptive research design was employed. The sample consisted of eight students, with two students representing each of the four learning styles: accommodating, assimilating, converging, and diverging. Data were collected through questionnaires, tests, and interviews. The research instruments included the Kolb Learning Style Inventory (KLSI), a mathematical literacy ability test, and an interview guide. Data analysis involved data reduction, data presentation, and conclusion drawing. The results revealed that students with accommodating and assimilating learning styles demonstrated proficiency in all three mathematical literacy indicators—formulate, employ, and interpret/evaluate—whereas students with a converging learning style met only two indicators (formulate and employ). In contrast, students with a diverging learning style fulfilled only one indicator (formulate). These findings suggest that students with accommodating and assimilating learning styles exhibited superior mathematical literacy skills compared to those with converging and diverging learning styles. This study contributes to the understanding of how different learning styles influence students' mathematical literacy and provides insights for educators to develop more effective teaching strategies tailored to diverse learning preferences.